Reacciones que se producen en la dinámica familiar ante la revelación de la orientación sexual diversa de uno de los hijos/as (2022)
The present research focuses on the effects that occur in the family dynamics before the revelation of the sexual diversity of one of the members. The methodology of this research is qualitative, and the information is collected through instruments such as semi-structured interviews and life history three participants with diverse sexual orientation aged 23, 24 and 27 4 years old; residents of the municipality of Cartago Valle.